L'impresa selvicolturale alla luce del decreto legislativo 3 aprile 2018, n. 34 "Testo unico in materia di foreste e filiere forestali" - Mauro, Mario (Strumenti per la didattica e la ricerca, 2020)
The Consolidated Law on forests and forest supply chains (Legislative Decree 34/2018) sets new balances in the management of national heritage forestry, introducing principles and rules to enhance its intrinsic multifunctionality. To achieve this, the concept of sustainable forest management is introduced, to which silviculture is delegated to provide a valuable contribution. The study investigates how a special legislation, oriented to give a systematic arrangement to the multiple public and private interests, that gravitate around the woods, can support silvicultural production, keeping in mind that silviculture has always been included in the Civil Code among the activities of the agricultural enterprise.